The chronic wound characterisation study and biobank: a study protocol for a prospective observational cohort investigation of bacterial community composition, inflammatory responses and wound-healing trajectories in non-healing wounds - Anne Kristine Servais Iversen; Klaus Kirketerp-Møller; Thomas Bjarnsholt; Hans Gottlieb; Blaine Gabriel Fritz; Mads Lichtenberg; Isabel Díaz-Pinés Cort; Dania Firas Al-Zoubaidi; Tim Holm Jakobsen (BMJ Open)
Introduction Chronic wounds affect 1%–2% of the global population, with rising incidence due to ageing and lifestyle-related diseases. Bacterial biofilms, found in 80% of chronic wounds, and scattered single-cell bacteria may hinder healing. Microbes are believed to negatively impact healing by exacerbating inflammation and host immune response.Methods and analysis The primary objective of the chronic wound characterisation (CWC) study is to investigate chronic wounds through a prospective observational cohort study exploring bacterial community composition, inflammatory responses and the influence of bacteria on wound-healing trajectories. The CWC study will be investigated through two cohorts: the predictive and in-depth.The predictive cohort includes patients with a chronic wound scheduled for mechanical debridement. The debrided material will be collected for dual RNA sequencing and 16s ribosomal RNA gene sequencing, as well as samples for microbial culturing and a photo to assess the wound. Clinical data is recorded, and healing and/or other clinical endpoints are established through medical records.The in-depth cohort includes and follows patients undergoing split-thickness skin grafting. Extensive sampling (ESwabs, biopsies, tape strips, debrided material and a sample of the skin graft) will be performed on surgery and patients will be seen at two follow-up visits. Samples will be analysed through culturing and next-generation sequencing methods. A biobank will be established comprising longitudinal clinical samples and clinical data.Ethics and dissemination The study has been approved by the board of health ethics, Capital Region of Denmark, under protocol number H-20032214. The study findings will be disseminated through peer-reviewed publications and showcased at both national and international conferences and meetings within the domains of microbiology, wound healing and infection.